Psychogenic Urinary Retention in Children: A Case Report - Kong-Sang Wan; Nai-Hsuan Liu; Chih-Kuang Liu; I-Zen Hwang (Pediatrics and Neonatology)
Psychogenic urinary retention occurs relatively infrequently in children and is less common than in adults. The influence of psychogenic factors on voiding generally results in an irritative syndrome, but rarely in urinary retention. A definitive diagnosis is established by excluding other pathological conditions. Evaluation includes urine culture, renal echography, spine magnetic resonance imaging, voiding cysto-urethrography, intravenous pyelography, and uroflowmetry. Here, we report on a 6-year-old girl with a 1-month history of voiding difficulty. Urology studies, including urine culture, revealed Escherichia coli, which was not present in preadmission urine cultures. Renal ultrasound and radiological images showed no gross abnormalities or vesicoureteral reflux, but uroflowmetry showed a low flow rate with residual urine. The results of imaging studies and pediatric psychiatric consultation led to a diagnosis of psychogenic urinary retention combined with urinary tract infection. Urinary rehabilitation included intermittent catheterization, bladder training, and supportive psychotherapy, after which the patient recovered and was discharged.